PSYCHOMETRIC PROPERTIES OF THE ANOMIA QUESTIONNAIRE (AQ) - Ļevina, Jeļena; Mārtinsone, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The purpose of this research was to develop the Anomia Questionnaire (AQ), which measures different dimensions of anomia and is based on the Levina, Martinsone, and Kamerade (Ļevina, Mārtinsone, & Kamerāde, 2015c, 2016a) integrative multidimensional model of anomia, as well as to determine its psychometric properties. The AQ was developed in Latvian. The sample consisted of 210 Latvian inhabitants aged from 19 to 58 years (27.6 % male, 72.4 % female). The factorial validity of the AQ was established using principal components analysis with Varimax rotation; this yielded six factors, which can be interpreted as Social Distrust (C1), Lack of Goal Clarity (C2), Generalized Sense of Meaninglessness (C3), Cultural Isolation (C4), Deviation from Prescribed Rules or Customs (C5), and Estrangement to Others (C6). All the AQ scales had high internal consistency (Cronbach’s alpha varied from .73 to .86). The reaction and discrimination indices satisfied the accepted psychometric criteria. The further stage of the AQ development would be the confirmatory factor analysis in broader international sample, the concurrent and convergent validity establishing, and test-retest reliability examination.